Anxiety and Clinical Practice Readiness of Student Nurses During Covid-19 Pandemic - David Hartadinata Pangaribuan; Putri Hapsari Kusumawati; Wulanlaka Tineke Tendean; Windy Sapta Handayani Zega; Ni Gusti Ayu Eka (Jurnal Keperawatan, 2022)
Clinical practice is a critical component of the nursing education program because it prepares graduates to be competent and professional nurses. Each student approaches clinical practice in hospitals with a unique level of readiness and anxiety, especially considering the recent Covid-19 pandemic situation. This study aimed to examine the relationship between anxiety and readiness for clinical practice in hospitals among nursing students. The descriptive correlational design was used in this study. There was a total of 337 second year nursing students. This study was conducted between February to March 2021. This study utilized the Casey-Fink Readiness for Practice Survey and the Hamilton Anxiety Rating Scale (HARS) questionnaires. The data were analyzed using the Chi-square test. Total of 201 nursing students involved in this study. Over half of the students (58.2 percent) reported experiencing anxiety at a mild to severe level. About 55.2 percent of students perceived ready for clinical practice in a hospital. This study reveals that there was a significant correlation between nursing students’ level of anxiety and their readiness for clinical practice at the hospital (p value 0.0001). Students are expected to be prepared for clinical practice to alleviate any anxiety. The more students prepare, the more confident they are in their ability to perform critical nursing activities.